Prognostic nutritional index and survival in prostate cancer: an updated systematic review and meta-analysis - Wang, Gang; Wu, Qihang; Chen, Telei (Frontiers in Nutrition, 2026)
ObjectiveTo evaluate the predictive value of the prognostic nutritional index (PNI) in prostate cancer patients. Compared with previous reviews, this study is the first to systematically grade and evaluate the quality of evidence regarding the association between PNI and prostate cancer prognosis using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) framework, which can provide more reliable and transparent evidence for clinical practice.MethodsA systematic search was conducted across PubMed, Embase, Web of Science, and Cochrane databases up to June 2025. Study quality was assessed using the Newcastle–Ottawa Scale. Outcomes included associations between PNI and overall survival (OS) and progression-free survival (PFS). Meta-analysis, Egger's test, and sensitivity analysis were performed using Review Manager 5.4.1 and Stata 15.1. The certainty of evidence for each outcome was evaluated and graded according to GRADE.ResultsThe systematic search identified 857 related studies, with 11 studies included in the meta-analysis. The meta-analysis revealed that a lower PNI was significantly associated with shorter OS (hazard ratio (HR): 2.03; 95% confidence interval (CI): 1.68, 2.46; P < 0.00001) and PFS (HR: 2.03; 95% CI: 1.65, 2.50; P < 0.00001). There was no significant publication bias for OS (P = 0.051), but there was significant publication bias for PFS (P = 0.014). Sensitivity analyses confirmed that the results for OS and PFS were stable and reliable. Regarding the certainty of evidence, OS was rated as moderate quality evidence, while the PFS was rated as low quality.ConclusionsLow PNI is associated with shorter OS and PFS in prostate cancer patients. Considering the inherent limitations of this study, more prospective studies are needed to confirm the association between PNI and the prognosis of prostate cancer patients.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251154118, identifier: CRD420251154118.